Pre-service teachers’ web pedagogical content knowledge and online information searching strategies - Güler Tuluk; İbrahim Kepceoglu (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study aimed to investigate the relationship between pre-service teachers’ web pedagogical content knowledge and online information searching strategies. In accordance with the aim, the correlational comparative survey method is used. The participants of the study are 220 university students from a faculty of education of a state university. The data of the study is gathered by Turkish versions of “Teachers’ Self-Efficacy toward the Web Pedagogical Content Knowledge Scale” and “Online Information Searching Strategy Inventory”. Canonical correlation analysis is used to determine the relationship between these two scales. As a result of the study, 17.3% common variance is determined between web pedagogical content knowledge and online information searching strategies.